The Concept of Work Ethic in Islam and Its Implications for Socio-Economic Development - Jagat Rayana; Aep Kusnawan; Muhamad Zuldin; Miftahul Huda (Yayasan Cendekia Gagayunan Indonesia, 2025)
This research aims to analyze the concept of work ethic from an Islamic perspective and examine the relevance of the values of the Qur'an and al-Sunnah in the formation of productive and responsible work behavior. This study is motivated by a view that associates the low work ethic of some Muslims with religious teachings, even though Islam normatively has a strong foundation in encouraging a high work culture. This research uses a library research method with a qualitative approach. Data was obtained from primary sources in the form of the Qur'an and al-Sunnah as well as various scientific literature that discusses work ethic and Islamic values. Data analysis is carried out through content analysis techniques to identify the concepts, principles, and values that are the basis of the Islamic work ethic. The results of the study show that the Islamic work ethic is built on fundamental values such as hard work, trust, discipline, responsibility, honesty, professionalism, and orientation to benefit. These values serve as an intrinsic source of motivation that encourages Muslim individuals to work optimally as a form of worship and devotion to Allah SWT. The findings of the study also show that the low work ethic found in some of the social practices of Muslims is more due to the lack of optimal understanding and internalization of Islamic teachings than to the weakness of Islamic theological doctrine itself. This study concludes that Islamic work ethic is a comprehensive and relevant value system in building a productive work culture, with integrity, and oriented towards the welfare of individuals and society.